Protective Effects of Pomegranate Juice on Nephrotoxicity Induced by Captopril and Gentamicin in Rats (Iranian Journal of Kidney Diseases, 2017)
Introduction. Nephrotoxicity is an important side effects of captopril and gentamicin. This study investigated the prophylactic and protective effects of pomegranate juice (PJ) on the kidney exposed to nephrotoxicity induced by these medications. Materials and Methods. Wistar male rats received drinking water (groups 1 to 3) or PJ at doses of 4 mL/kg (group 4), 10 mL/kg (groups 5 and 7), and 15 mL/kg (group 6) for 14 days. Captopril and gentamicin were administrated on days 10 and 14 to groups 1 and 2, respectively, while groups 3 to 6 received both. Group 7 did not receive anything. The serum, urine, and renal tissue parameters were measured after the experiment. Results. Group 1 (captopril) had a higher malondialdehyde level than groups 4, 5, 6, and 7 with PJ (P